2015
DOI: 10.1002/etc.3099
|View full text |Cite
|
Sign up to set email alerts
|

Fate of polychlorinated biphenyls in a contaminated lake ecosystem: Combining equilibrium passive sampling of sediment and water with total concentration measurements of biota

Abstract: Equilibrium sampling devices can be applied to study and monitor the exposure and fate of hydrophobic organic chemicals on a thermodynamic basis. They can be used to determine freely dissolved concentrations and chemical activity ratios and to predict equilibrium partitioning concentrations of hydrophobic organic chemicals in biota lipids. The authors' aim was to assess the equilibrium status of polychlorinated biphenyls (PCBs) in a contaminated lake ecosystem and along its discharge course using equilibrium s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 67 publications
(119 reference statements)
1
12
0
Order By: Relevance
“…Jahnke et al (2012) also found that Clipid,partition of PCBs were about five times higher than Clipid,biota in fish from Baltic Sea. Moreover, Clipid,partition of PCBs were higher than Clipid,biota in mussels and fish (Jahnke et al, 2014b, Mäenpää et al, 2015b, Schäfer et al, 2015, but hexachlorobenzene was approaching equilibrium (Jahnke et al, 2014a). Overall, Clipid,partition were generally higher than Clipid,biota, implying accumulation of HOCs in most field-collected organisms didn't achieve equilibrium.…”
Section: Application Of Partition Coefficients Between Biological Phamentioning
confidence: 98%
“…Jahnke et al (2012) also found that Clipid,partition of PCBs were about five times higher than Clipid,biota in fish from Baltic Sea. Moreover, Clipid,partition of PCBs were higher than Clipid,biota in mussels and fish (Jahnke et al, 2014b, Mäenpää et al, 2015b, Schäfer et al, 2015, but hexachlorobenzene was approaching equilibrium (Jahnke et al, 2014a). Overall, Clipid,partition were generally higher than Clipid,biota, implying accumulation of HOCs in most field-collected organisms didn't achieve equilibrium.…”
Section: Application Of Partition Coefficients Between Biological Phamentioning
confidence: 98%
“…Monitoring alongside biota Sediments and overlying waters PCBs SR and LDPE deployed in various lake and river sediments and overlying waters alongside biota to monitor the concentration of a range of HOCs and assess the bioaccumulation prediction capacity of each device for biota at a range of trophic levels. [229,309] River waters PAHs; PCBs; pesticides SR deployed in rivers alongside resident macroinvertebrates and attached to captured fish (flathead catfish) to measure water concentrations and exposure of biota through chemical analysis of PSD extracts and biota tissues for a range of HOCs.…”
Section: Coastal Watersmentioning
confidence: 99%
“…Jars coated with a silicone polymer on the inner vertical walls have been used for passive sampling of PAHs in soils 36 and hexachlorobenzene and PCBs in sediment. 18,19,37 Coating of 180 mL amber glass jars was done as described by Reichenberg et al, 36 with slight modications. Jars were rolling horizontally and a (Dow Corning® 1-2577) polymer-pentane solution was added to the jars.…”
Section: Preparation Of Equilibrium Passive Sampling Jars and Dosing mentioning
confidence: 99%
“…The jars were rinsed with Milli-Q water, wiped and dried thoroughly with lint-free tissues. 37 The chemicals in the polymer were extracted with 3 mL solvent by rolling the jars horizontally for 30 min. 18 We used a 1 : 1 mixture of acetone:n-hexane for extracting HOCs from the polymer inside the jars, instead of n-hexane only as previously used by Jahnke et al (where 3-7 Cl PCBs were targeted 18 ), since we aimed to capture a wider range of chemicals.…”
Section: Validation Of Equilibrium Partitioning In Sampling Jarsmentioning
confidence: 99%